Medication organizers (pill minders) increase the risk for unintentional pediatric ingestions - Wang, George Sam; Hoppe, Jason A.; Brou, Lina; Heard, Kennon J. (Clinical toxicology (Philadelphia, Pa.), 2017)
Objective: Medication organizers may help improve medication compliance; however, they may increase the risk of having an unintentional pediatric exposure. The objective of this study was to measure the association between a pediatric emergency department (ED) visit for an unintentional pharmaceutical ingestion and the use of a medication organizer in the household. Methods: This was a cross-sectional case control study at a tertiary care children's hospital ED. Cases included subjects <6 years of age who were evaluated in the ED for an unintentional pharmaceutical ingestion. The control group presented to the ED for a non-injury complaint and was matched using age and sex. Results: The unadjusted odds ratio (OR) of risk for unintentional pharmaceutical ingestion with use of a medication organizer was 2.0 (95% CI, 1.3, 2.9). After adjusting for the presence of prescription medications in the home, the OR of risk for ingestion remained statistically significant at 1.8 (95% CI, 1.1, 2.7). The child obtained the exposure medication from the medication organizer in 63% of cases where a medication organizer was present in the home. Cases were more likely to have knowledge of, and previous contact with poison control centers (PCC) than non-injury controls. Overall, a large number of caregivers (36%) did not have any knowledge of PCC. There were also differences in smoking and use of seat belts between cases and controls. Conclusions: The use of medication organizers may be a risk factor for unintentional pediatric pharmaceutical ingestions, even when controlling for the use of prescription medications in the home. Further research is needed to evaluate the specific role of medication organizers, and subsequently, improve prevention strategies.